A Study on the Use of Cephalosporins in Patients with Diabetic Foot Infections - Balakrishna, Prathap; Shah, Dharati; Kishore, Githa; Keerthi, Sneha (Indian Journal of Pharmacy Practice)
Diabetic foot problems such as ulcerations, infections and gangrene are dreadful complications of diabetes mellitus and a major cause of hospitalization. Overall 15% of individuals with diabetes mellitus will have foot ulcers during their lifetime. Diabetic foot infected patients are usually prescribed with broad spectrum antibiotics. Our study was done to evaluate the sensitivity pattern of cephalosporins in diabetic foot patients and to assess their prescribing patterns. We carried out a prospective study in the surgery department of a tertiary care hospital on 77 patients who had diabetic foot infections. Prescribing patterns of cephalosporins and wound culture and sensitivity testing on these patients was studied for a period of 6 months. Staphylococcus aureus was the most common gram positive pathogen isolated, E.coli, Klebsiella, Pseudomonas and Citrobacter were the common gram negative organisms isolated. Ceftriaxone was the most commonly prescribed antibiotic. Sensitivity pattern showed that 41.5% of gram positive cocci and 25% of gram negative bacilli were sensitive to Ceftriaxone. Ceftriaxone in our study was found to be an effective drug provided appropriate barrier techniques were used to prevent nosocomial spread. Organisms which were originally sensitive developed resistance approximately in a span of two weeks, probably due to antibiotic pressure. Hence there should be an active infection control team which can monitor the prevalent organisms and their antibiograms and periodically inform the clinicians. The pharmacists should also be included in the team, apart from the microbiologist, the surgeon and the nursing staff.
Keywords: Cephalosporins; Diabetes; Diabetic foot infections; Prescribing patterns; Sensitivity pattern